Greenness and Whiteness Assessed Mathematically Filtered UV Spectroscopic Approaches for Quality Control of Amlodipine, Telmisartan and Metoprolol from Ternary Formulation - Attimarad, Mahesh; Sreehari, Krishna Swaroop Duddi; Aldhubiab, Bandar (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Latest studies highlight the effectiveness of a new combination tablet that contains Amlodipine (AML), Telmisartan (TEL), and Metoprolol (MET) for the treatment of hypertension. The present work demonstrates the establishment of efficient and environmentally friendly sensitivity-enhanced UV spectroscopic approaches for the concomitant assessment of tablet preparations of AML, TEL, and MET. Materials and Methods: In order to disentangle the complex ternary mixture, the double devisor spectroscopic method at two chosen wavelengths was established. The second technique measures the apex height of the ratio first derivative spectrum's at specific wavelengths among a number of maxima and minima. The ecological profile of the methods was also assessed, taking into account two factors: whiteness using RGB12 and greenness using AGREE and the hexagonal tool. Results: The sensitivity of the low-concentration analyte AML and low-peak amplitude analyte MET was increased by the scaling factor. AML, TEL, and MET have all been effectively analyzed using these methods, with results falling into the ranges of 1-10 μg/mL, 5-30 μg/mL, and 5-40 μg/mL, correspondingly. Additionally, we followed ICH guidelines to validate these approaches for specificity, accuracy, and precision. No statistically significant differences were seen when compared to the described HPLC approach. Conclusion: The recommended methods have been found to be safe, economically feasible, and sustainable based on the ecological assessment by RGB12, AGREE and hexagonal methods. Therefore, the proposed UV spectroscopic approaches could be utilized regularly for analysis of formulation comprising AML, TEL, and MET.
Keywords: Hypertension; Amlodipine; Telmisartan; Metoprolol; UV-derivative spectroscopy; Greenness